The Warren Buffett CEO secrets from the Berkshire Hathaway managers - Miles, Robert P. (John Wiley & Sons, 2002)
Warren Buffet has said that investors need only look at his operating companies to understand his investment approach. This book provides them with that exclusive look. Berkshire Hathaway insider, Robert Miles draws upon his own experiences and those of Berkshire executives, to provide a look at the Berkshire culture and its management principles.